2013
DOI: 10.1021/jp312029e
|View full text |Cite
|
Sign up to set email alerts
|

Exciplex Formation in Blended Spin-Cast Films of Fluorene-Linked Dyes and Bisphthalimide Quenchers

Abstract: Spin-cast films of dyes (donor-π-donor, donor-π-acceptor, and acceptor-π-acceptor type, where the donor is Ph2N-, the acceptor is 2-benzothiazoyl, and the π-linker is 9,9-diethylfluorene) blended with nonconjugated bisphthalimides were prepared. Upon visible-light excitation of the dyes, quenching of the excited state occurs by exciplex formation between dye and bisphthalimide molecules or, in some cases, by excimer formation or aggregation-induced emission between two dye molecules. The extent of exciplex for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…It is interesting that the fastest decay component has a lifetime (0.9 ns) even shorter than those of the constituting molecules (2.6 ns for NPB and 5.0 ns for DPTPCz). This has been explained by Jankus et al and Stewart et al, who propose that the fastest decay component occurs due to quenching of the S 1 of the constituting molecules . On the other hand, the other two mixed films do not show any decay component faster than their constituting molecules.…”
Section: Summary Of High‐efficiency Oleds With Delayed Fluorescencementioning
confidence: 75%
See 2 more Smart Citations
“…It is interesting that the fastest decay component has a lifetime (0.9 ns) even shorter than those of the constituting molecules (2.6 ns for NPB and 5.0 ns for DPTPCz). This has been explained by Jankus et al and Stewart et al, who propose that the fastest decay component occurs due to quenching of the S 1 of the constituting molecules . On the other hand, the other two mixed films do not show any decay component faster than their constituting molecules.…”
Section: Summary Of High‐efficiency Oleds With Delayed Fluorescencementioning
confidence: 75%
“…Figure shows the exciplex formation process and related energy relationships. The driving force (–Δ G cs ) for exciplex formation in the solid state can be estimated based on a modified Rehm–Weller equation, which is given approximately by the difference in the exciton energy ( E A* or E D* ) of the constituting molecules with the exciplex energy ( E exciplex ) Equation . ΔGcs= Eexciton(EA* or ED*)Eexciplex E exciplex are determined from the PL peak maxima (Figure ) of the TAPC:DPTPCz, the TCTA:DPTPCz and the NPB:DPTPCz films to be 2.47 (503 nm), 2.47 (502 nm), and 2.53 (491 nm) eV, respectively.…”
Section: Summary Of High‐efficiency Oleds With Delayed Fluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…These dyes have been studied previously in our group in spin-cast films blended with bisphthalimides for exciplex formation. 29,30 Solvent dependent studies by Belfield et al on similar dyes 31 and BT2F 32 revealed strong solvatochromism on the emission spectra of D-π-A derivatives, but little dependence in symmetrical molecules. They also showed that a solventstabilized state is formed in the asymmetrical fluorene, but showed no direct evidence of this process.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] They have indeed been invoked in intra- [6][7][8][9][10] and intermolecular electron transfer in solution, [11][12][13][14][15][16][17] in organic semiconductors for photovoltaics, [18][19][20][21][22][23] and organic light emitting diodes, [24][25][26][27][28] and in biological systems like DNA [29][30][31][32] and photosynthetic reaction centers, 33 some time under different names, such as charge-transfer excitons or excited chargetransfer complexes. All these monikers designate a species with an electronic structure between those of the reactants and products.…”
Section: Introductionmentioning
confidence: 99%